A woman in Arabia : the writings of the Queen of the Desert - Bell, Gertrude Lowthian, 1868-1926; Howell, Georgina, 1942- (New York, Penguin Books, 2015)
"A portrait in her own words of the female Lawrence of Arabia. One of the great woman adventurers of the twentieth century and the chief architect of British policy in the Middle East after World War I, Gertrude Bell turned her back on Victorian society to study at Oxford and travel the world. Mountaineer, archaeologist, Arabist, writer, poet, linguist, and spy, she dedicated her life to championing the Arab cause and was instrumental in drawing the borders that define today's Middle East. As she wrote in one of her letters, "It's a bore being a woman when you are in Arabia." Forthright and spirited, opinionated and playful, and deeply instructive about the Arab world, this volume brings together Bell's letters, military dispatches, diary entries, and travel writings to offer an intimate look at a woman who shaped nations."--Back cover
The linguist -- The poet -- The "person" -- The mountaineer -- The archaeologist -- The desert traveler -- The lover -- The prisoner -- The war worker -- The intrusives -- The nation builder -- The kingmaker -- The courtier
Includes index
Keywords: Bell, Gertrude Lowthian, -- 1868-1926; Travelers -- Middle East -- Biography; Women travelers -- Middle East -- Biography; Archaeologists -- Great Britain -- Biography; Women archaeologists -- Great Britain -- Biography; Asianists -- Biography; Women Asianists -- Biography; Colonial administrators -- Great Britain -- Biography; Colonial administrators -- Middle East -- Biography; Middle East -- Politics and government -- 1914-1945; Middle East -- History -- 20th century; Biography; History